Role of afferent neurons in stress induced degenerative changes of the bladder - ERCAN, FERİHA (ELSEVIER SCIENCE INC, 2001)
Purpose: We investigated the role of afferent C fibers in morphological changes of the rat bladder during stress. Materials and Methods: Wistar albino rats were exposed to cold immobilization stress. Different routes of capsaicin administration before cold immobilization stress were studied. Capsaicin was given to neonates, around the vagus (perivagal) or celiac (periceliac), or perivagal plus periceliac. From each group samples of bladder were randomly chosen for morphological evaluation using electron microscopy. Results: Stress exposure led to pathological changes, including an increased number of mast cells, degenerated urothelium and dilated tight junctions, in the bladder. Capsaicin given neonatally and around the vagal and celiac ganglia prevented these stress induced degenerative bladder changes. Conclusions: Activation of capsaicin sensitive afferent neurons locally and centrally may be involved in stress related pathological changes in the rat bladder.
Keywords: capsaicin; stress; bladder; RAT URINARY-BLADDER; SUBSTANCE-P; INTERSTITIAL CYSTITIS; CAPSAICIN; SYSTEM; PATHOPHYSIOLOGY; INNERVATION; GANGLIA; AXONS